Edukasi Pemberian Terapi Uap Sederhana untuk Bersihan Jalan Napas Tidak Efektif pada ISPA - Hapipah Hapipah; Istianah Istianah (Jurnal Abdimas Kesehatan (JAK), 2023)
Acute respiratory infection (ARI) is one of the public health problems that is important to pay attention to. ARI is an infection that occurs in the respiratory tract, both upper and lower respiratory tract. This infection can cause symptoms of cough, runny nose, and fever. The problem that often arises in this ARI is ineffective airway clearance due to hypersecretion in the respiratory tract. Interventions are carried out to maintain a patent airway so that you can breathe spontaneously without difficulty, pain is reduced and oxygen needs are met. One of the efforts to overcome airway clearance is not effective because of nasal congestion can be done with simple steam therapy with eucalyptus oil. This community service aims to train the community's independence in dealing with health problems experienced, especially related to ARI with simple steam therapy with eucalyptus oil. This activity was carried out on December 19, 2021 in Sesela village, West Lombok district with 43 participants. The method of implementation is through lectures, discussions and demonstrations. The results of the evaluation of this activity showed that participants were able to understand and understand the meaning, signs and symptoms, causes and management of ARI and understand and know how to do simple steam therapy with eucalyptus oil.